In the previous chapter we have seen a general overview of the operational amplifier. In this chapter, we will see
that depending on the topology used, the configuration acquires a proper name. Let's look at the topology called operational
amplifier in the adder configuration.
2. The Adding Operational Amplifier
In this configuration the non-inverting input is grounded, therefore
V2 = 0. As we have two entrances, Va and Vb,
connected to the node V1, we can solve this circuit by applying
the law of nodes for that node.
Figure 44-01
In the Figure 44-01, we see the adder circuit. As indicated in the circuit,
ii = 0, so we can write for the node V1:
ii + i2 + if = 0
Now, by applying the nodal analysis for this node, we have:
(Va - V1)/R1 + (Vb - V1)/R2 +
(Vo - V1)/Rf = 0
But we know that V1 = 0. So, isolating Vo
we arrive at the desired equation that allows to calculate the output voltage as a function of the input voltages Va and Vb.
eq. 44-01
By the equation we see that the output voltage is determined by the ratio between the resistor
Rf and the resistor of each input. We can define the quotient of resistances as a weighted factor and represent it as follows:
eq. 44-02
So we can generalize to "n" entries and we get:
eq. 44-03
3. The Non-Inverting Adder
In this item we will analyze the adder in the Non-Inverting configuration. Let's start from a general circuit as shown in the Figure 44-02, initially, with three voltage sources at the non-inverting input.
Figure 44-02
For the analysis of this circuit we must consider the operational amplifier as ideal and therefore satisfying the following initial conditions:
Zi = ∞ | iin = 0 | Va = Vb
In addition, by the law of Kirchhoff for nodes, we have:
Let's adopt the following equality: Z = R1 = R2 = R3. So we get the relation:
(V1 + V2 + V3 - 3 Vb ) / Z = 0
Solving this relationship, we obtain:
V1 + V2 + V3 = 3 Vb
On the other hand, using the fact that Va = Vb, we can write:
Vb = Vo ( R / ( R + Rf )
Substituting this relation in the previous equation we obtain:
V1 + V2 + V3 = 3 Vo [ R / ( R + Rf ]
By making Rf = 2 R we can rewrite the above equation as:
Vo = V1 + V2 + V3
This equation was developed for the case of three sources in the input, however we can generalize it to
n sources, as long as the following condition is maintained:
Rf = (n - 1 ) R
If this condition is observed, then we can write that: